Multidetector Computed Tomography (MDCT) Evaluation of Traumatic Brain Injury in Head Trauma Patients in Tertiary Hospital of Eastern Region of Nepal - Yadav, Ajay Kumar; Dev, Binit; Taparia, Sushil; Kumar, Parvez; Mandal, Rakesh; Vaidya, Bivek (Birat Journal of Health Sciences, 2021)
Introduction: Traumatic brain injury (TBI) in patients with head trauma is common cause for emergency visits to hospital affecting all age groups. It is one of important leading cause of death and disability worldwide besides leading to neurological disease burden. Noncontrast enhanced Multidetector computed tomography (MDCT) is imaging modality of choice for detection of various intracranial lesions. Objectives: This study was done to analyse various imaging findings on MDCT in traumatic head injury patients along with association of CT findings with clinical manifestation and mechanism of injury. Methodology: In this ethically approved prospective study, CT scan was done in 224 consecutive patients with head injury from November 2020 to February 2021. The various imaging findings seen in CT scan were documented in proforma. The data collected was analyzed with appropriate statistical test and statistical significance was calculated. Results: Total of 224 patients with diagnosis of head injury were included in the study. The male to female ratio was 2.86 and most common age group involved was between 20-40years (41.1%). The most common mode of injury was road traffic accidents (57.6%) and most of the patients presented with history of altered sensorium (35.7%). About 47.3% patients showed abnormal findings on CT scan with scalp lesion was most common findings (82%) followed by skull fractures (54.7%) and cerebral contusions (43.4%). Patients with history of RTA had more abnormal CT scan (62%) than fall injury and physical assault. Statistically significant association seen between CT scan findings with Glasgow Coma Scale and RTA (P<0.05). Conclusion: The present study showed well documented role of CT scan in diagnosis of TBI besides detection of spectrum of intracranial lesions in patients with head trauma. Road traffic accident is most common mode of head injury with most of the victims are young middle age active male.